2014
DOI: 10.1111/ajco.12190
|View full text |Cite
|
Sign up to set email alerts
|

National Working Group Meeting on ALK diagnostics in lung cancer

Abstract: The global landscape of molecular testing is rapidly changing, with the recent publication of the International Association for the Study of Lung Cancer (IASLC)/College of American Pathologists (CAP) guidelines and the ALK Atlas. The IASLC/CAP guidelines recommend that tumors from patients with non-small cell lung cancer (NSCLC) be tested for ALK rearrangements in addition to epidermal growth factor receptor (EGFR) mutations. The spur for this recommendation is the availability of novel therapies that target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The principle of IHC is based on the fact that activating ALK rearrangements are accompanied by significant overexpression of the catalytic portion of this tyrosine kinase. IHC is generally capable of producing highly reliable results when performed in reference laboratories; however, it requires the standardization of reagents and protocols across pathology laboratories . The Ventana ALK assay used D5F3 antibody is a resultful method of detecting ALK rearrangement.…”
Section: Alk Rearrangement Detection Methods In Nsclc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of IHC is based on the fact that activating ALK rearrangements are accompanied by significant overexpression of the catalytic portion of this tyrosine kinase. IHC is generally capable of producing highly reliable results when performed in reference laboratories; however, it requires the standardization of reagents and protocols across pathology laboratories . The Ventana ALK assay used D5F3 antibody is a resultful method of detecting ALK rearrangement.…”
Section: Alk Rearrangement Detection Methods In Nsclc Patientsmentioning
confidence: 99%
“…IHC is generally capable of producing highly reliable results when performed in reference laboratories; however, it requires the standardization of reagents and protocols across pathology laboratories. [55][56][57][58] The Ventana ALK assay used D5F3 antibody is a resultful method of detecting ALK rearrangement. The Ventana ALK (D5F3) CDx Assay (Ventana Medical Systems, Tucson, AZ, USA) was approved by the US FDA in 2015 as a companion detection test for the use of crizotinib.…”
Section: Types Of Oncogenesis In Alkmentioning
confidence: 99%
“…FISH requires significant time input of an extensively trained personnel and cannot be subjected to a reasonable automation; furthermore, it demonstrates relatively high failure rates at least in some sample series and may provide poorly interpretable results in a noticeable fraction of NSCLC cases. In addition, FISH always relies on the purchase of commercial kits, which are highly expensive [2,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of IHC is based on the fact that activating ALK rearrangements are accompanied by significant overexpression of the catalytic portion of this tyrosine kinase. IHC is generally capable to produce highly reliable results when performed in reference laboratories, however its interlaboratory reproducibility and performance in heterogenous lung cancer tissue collections remains to be evaluated [8,9,[11][12][13][14]. Use of PCR-based assays is also a common approach for ALK testing.…”
Section: Introductionmentioning
confidence: 99%
“…ALK rearrangement occurs in approximately 5% of all lung adenocarcinomas and 1.3% of lung squamous cell cancer (SqCC), whereas ROS1 rearrangement accounts for 1% to 3% of all lung adenocarcinomas and rarely, has been reported in lung SqCC. 1,2 Crizotinib has been approved by the U.S. Food and Drug Administration for treating patients with advanced-stage ALK-positive or ROS1-positive NSCLCs. Some case reports have also shown that patients with lung SqCC with ALK or ROS1 rearrangements respond to crizotinib treatment.…”
Section: Introductionmentioning
confidence: 99%